Advances in sensing, response and regulation mechanism of salt tolerance in rice - Ponce, Kimberly S.; Guo, Longbiao; Leng, Yujia; Meng, Lijun; Ye, Guoyou (MDPI, 2021)
Soil salinity is a serious menace in rice production threatening global food security. Rice responses to salt stress involve a series of biological processes, including antioxidation, osmoregulation or osmoprotection, and ion homeostasis, which are regulated by different genes. Understanding these adaptive mechanisms and the key genes involved are crucial in developing highly salt-tolerant cultivars. In this review, we discuss the molecular mechanisms of salt tolerance in rice—from sensing to transcriptional regulation of key genes—based on the current knowledge. Furthermore, we highlight the functionally validated salt-responsive genes in rice.